2004
DOI: 10.1007/s00213-003-1594-8
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled study of sertraline in the treatment of outpatients with seasonal affective disorder

Abstract: Sertraline pharmacotherapy has been demonstrated to be an effective and well-tolerated therapy for out patients with SAD. As such, sertraline offers an important pharmacological option in the clinical management of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…Enhanced 5-HTT function as suggested by the present data may be an important mechanism contributing to low synaptic serotonin levels during depression, since it presumably leads to enhanced synaptic serotonin clearance. This mechanism is compatible with the known antidepressant effects of 5-HTT blockade in seasonal (Lam et al, 2006;Moscovitch et al, 2004) and nonseasonal (Axelrod and Inscoe, 1963) depression. Our data suggest that changes in 5-HTT efficiency are a meaningful and naturally occurring physiological process that is altered in patients with SAD, and they show that changes in 5-HTT efficiency occur parallel to changes in depressive symptoms.…”
Section: Resultssupporting
confidence: 84%
“…Enhanced 5-HTT function as suggested by the present data may be an important mechanism contributing to low synaptic serotonin levels during depression, since it presumably leads to enhanced synaptic serotonin clearance. This mechanism is compatible with the known antidepressant effects of 5-HTT blockade in seasonal (Lam et al, 2006;Moscovitch et al, 2004) and nonseasonal (Axelrod and Inscoe, 1963) depression. Our data suggest that changes in 5-HTT efficiency are a meaningful and naturally occurring physiological process that is altered in patients with SAD, and they show that changes in 5-HTT efficiency occur parallel to changes in depressive symptoms.…”
Section: Resultssupporting
confidence: 84%
“…Antidepressant medication is a second effective treatment for SAD (see Lam et al, 1995;Moscovitch et al, 2004), and it is appropriate to consider whether the predictions of the PSH are also confirmed with this intervention. Two hypotheses were therefore tested.…”
Section: Introductionmentioning
confidence: 98%
“…Serotonergic agents working via different mechanisms to enhance 5-HT neurotransmission, including d-fenfluramine (O'Rourke et al, 1987) and selective serotonin reuptake inhibitors (Moscovitch et al, 2004), have been found to be effective in the treatment of SAD. Moreover, circadian and 5-HT-related polymorphisms have been reported in people with SAD (Johansson et al, 2003).…”
Section: The 5-ht 1b Ko Mouse As a Model For Seasonal Affective Disormentioning
confidence: 99%